Implementasi Kurikulum Merdeka di Sekola Dasar Negeri Tuntang 04 Kecamatan Tuntang Kabupaten Semarang - Indah Wahyu Hidayati; Noor Miyono; Sumarno (CENDEKIAWAN, 2025)
The purpose of this study is to describe (1) the planning of the independent curriculum at Tuntang 04 State Elementary School, Tuntang District, Semarang Regency, (2) the implementation of the independent curriculum at Tuntang 04 State Elementary School, Tuntang District, Semarang Regency, and (3) the evaluation of the independent curriculum at Tuntang 04 State Elementary School, Tuntang District, Semarang Regency. This study uses a qualitative descriptive method with a case study approach, the subjects of this study are the principal, teachers, and the KSP development team. Data collection techniques are interviews, documentation and observation. The data analysis used is qualitative analysis including data collection, data reduction, data display and drawing conclusions. The results of the study showed that (1) Curriculum planning at SDN Tuntang 04 Semarang Regency began with coordination with the education office and a KSP preparation meeting involving all existing stakeholders, learning planning began with a diagnostic assessment of students, teachers designed learning programs, while P5 planning was carried out by the P5 facilitator team, (2) Curriculum implementation was marked by the implementation of differentiated learning but was still constrained by limited time, (3) Evaluation of the independent curriculum was marked by teachers conducting summative and formative assessments. The suggestion is that differentiated learning be improved in order to improve students' academic achievement and communication skills and make students more enthusiastic about learning.